Interaction With Fungi Promotes the Accumulation of Specific Defense Molecules in Orchid Tubers and May Increase the Value of Tubers for Biotechnological and Medicinal Applications: The Case Study of Interaction Between Dactylorhiza sp. and Tulasnella calospora - Hampejsová, Romana; Berka, Miroslav; Berková, Veronika; Jersáková, Jana; Domkářová, Jaroslava; von Rundstedt, Friederike; Frary, Anne; Saiz-Fernández, Iñigo; Brzobohatý, Břetislav; Černý, Martin (Frontiers in Plant Science, 2022)
Terrestrial orchids can form tubers, organs modified to store energy reserves. Tubers are an attractive source of nutrients, and salep, a flour made from dried orchid tubers, is the source of traditional beverages. Tubers also contain valuable secondary metabolites and are used in traditional medicine. The extensive harvest of wild orchids is endangering their populations in nature; however, orchids can be cultivated and tubers mass-produced. This work illustrates the importance of plant-fungus interaction in shaping the content of orchid tubers in vitro. Orchid plants of Dactylorhiza sp. grown in asymbiotic culture were inoculated with a fungal isolate from Tulasnella calospora group and, after three months of co-cultivation, tubers were analyzed. The fungus adopted the saprotrophic mode of life, but no visible differences in the morphology and biomass of the tubers were detected compared to the mock-treated plants. To elucidate the mechanisms protecting the tubers against fungal infestation, proteome, metabolome, and lipidome of tubers were analyzed. In total, 1526, 174, and 108 proteins, metabolites, and lipids were quantified, respectively, providing a detailed snapshot of the molecular process underlying plant-microbe interaction. The observed changes at the molecular level showed that the tubers of inoculated plants accumulated significantly higher amounts of antifungal compounds, including phenolics, alkaloid Calystegine B2, and dihydrophenantrenes. The promoted antimicrobial effects were validated by observing transient inhibition of Phytophthora cactorum growth. The integration of omics data highlighted the promotion of flavonoid biosynthesis, the increase in the formation of lipid droplets and associated production of oxylipins, and the accumulation of auxin in response to T. calospora. Taken together, these results provide the first insights into the molecular mechanisms of defense priming in orchid tubers and highlight the possible use of fungal interactors in biotechnology for the production of orchid secondary metabolites.